Neanthes goodayi sp. nov. (Annelida, Nereididae), a remarkable new annelid species living inside deep-sea polymetallic nodules - Drennan, Regan; Wiklund, Helena; Rabone, Muriel; Georgieva, Magdalena N.; Dahlgren, Thomas G.; Glover, Adrian G. (European Journal of Taxonomy, 2021)
A new species of abyssal Neanthes Kinberg, 1865, N. goodayi sp. nov., is described from the Clarion-Clipperton Zone in the central Pacific Ocean, a region targeted for seabed mineral exploration for polymetallic nodules. It is a relatively large animal found living inside polymetallic nodules and in xenophyophores (giant Foraminifera) growing on nodules, highlighting the importance of the mineral resource itself as a distinct microhabitat. Neanthes goodayi sp. nov. can be distinguished from its congeners primarily by its distinctive, enlarged anterior pair of eyes in addition to characters of the head, pharynx and parapodia. Widespread, abundant, and easily recognisable, N. goodayi sp. nov. is also considered to be a suitable candidate as a potential indicator taxon for future monitoring of the impacts of seabed mining.